Association of Serum Alpha-Tocopherol and Retinol with the Extent of Coronary Lesions in Coronary Artery Disease - Carolinne Thaísa de Oliveira Fernandes Miranda; Victor Hugo Rezende Duarte; Marina Sampaio de Menezes Cruz; Mychelle Kytchia Rodrigues Nunes Duarte; Jéssica Nayara Góes de Araújo; Ayda Maria Quirino Silva dos Santos; Juliana Marinho de Oliveira; Maria Sanali Moura Oliveira Paiva; Adriana Augusto Rezende; Mario Hiroyuki Hirata; Rosario Dominguez Crespo Hirata; Karla Danielly da Silva Ribeiro; et al. (Journal of Nutrition and Metabolism)
Background and aims: Fat-soluble vitamins play an important role in the pathogenesis of cardiovascular disease and progression of atherosclerosis. This study aimed at investigating the relationship of the serum levels of alpha-tocopherol and retinol with the extent of coronary lesions in patients with coronary artery disease. Methods. Patients with coronary artery disease (n=177) aged 30–74 years, who underwent their first coronary angiography, were enrolled. The extent of coronary lesions was assessed using the Friesinger index (FI). Accordingly, patients were grouped as follows: FI = 0–4 (n=90), FI = 5–9 (n=50), and FI = 10–15 (n=37). Serum levels of vitamins were ‬determined via high-performance liquid chromatography and serum biochemical analysis. Results. Assessment of FI-based groups revealed that 50.8% patients had a coronary artery lesion to a low extent (FI 0–4). Individuals in this group were younger and had lower glucose and serum alpha-tocopherol levels than the other groups (p<0.05). Low levels of alpha-tocopherol were more frequent in the FI 0–4 group than that in the other groups (p=0.03). No difference was observed between the mean serum retinol levels among the FI-based groups (n=0.492), and the low frequency of retinol was consistent among the FI groups (n=0.348). Conclusions. The low level of alpha-tocopherol together with the presence of dyslipidemia is probably associated with the initial events in atherosclerosis. Increased alpha-tocopherol levels in patients with more extensive coronary artery lesions may have resulted from altered vitamin E metabolism with increased oxidative stress.